Strength analysis of a container semi-truck frame. (September 2021) - Caban, Jacek; Nieoczym, Aleksander; Gardyński, Leszek
Highlights: Analytical calculations of the values of forces and stresses on the semi-trailer frame and verification of the calculations carried out with the use of FEM for the selected two variants of work were performed. An accidental random factor may have contributed to the accident, e.g. in the form of a sudden lateral wind during unloading of the trailer. The probable cause of damage to the semi-trailer as a result of breaking the right longitudinal frame was an incorrect manufacturing technology, in the form of butt welded I-beam belts constituting the longitudinal frame, with extremely low quality joints. Abstract: The article presents an analysis of the causes for the occurrence of a fracture of a tipping semi-trailer frame in a lifted position. On the basis of an external examination of the damage parts hypotheses of the causes of the error were formulated. The formulation as well as analytical calculations were necessary due to incomplete information regarding the unloading conditions, that is flatness of the surface, wind, the usage of side support brackets. The values of force and stress in side-brackets of the semi-trailer were calculated. On their basis the cause of the fracture was determined. In order to verify the analytical calculations, a strength analysis using FEM was conducted in the case of unloading from a flat or tipped semi-trailer.